2020
DOI: 10.1017/cts.2020.3
|View full text |Cite
|
Sign up to set email alerts
|

Building capacity for dissemination and implementation to maximize research impact in a CTSA: The University of Wisconsin story

Abstract: AbstractWe report results of an 8-year process of stakeholder engagement aimed at building capacity in Dissemination and Implementation (D&I) research at the University of Wisconsin as part of the National Institutes of Health’s Clinical and Translational Science Award (CTSA). Starting in 2008, annual individual interviews were held with leaders of the Wisconsin CTSA’s community engagement core for strategic planning purposes. Interviews were followed by annual planning mee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…CTSAs can also leverage existing structures to integrate D&I training and research (e.g., community engagement core, workforce development, evaluation) [10]. There are excellent exemplars to learn from in building capacity for D&I research within CTSAs through community engagement [47]. For example, community engagement and practice-based research networks (PBRNs) [48] are central to D&I, and many CTSAs already have expertise in community engagement, PBRNs, and existing Community Advisory Boards, which D&I researchers could learn from as part of "best practices" in engaging with and learning from existing networks of patients, clinicians, or other community partners.…”
Section: Ctsa Site Characteristicsmentioning
confidence: 99%
“…CTSAs can also leverage existing structures to integrate D&I training and research (e.g., community engagement core, workforce development, evaluation) [10]. There are excellent exemplars to learn from in building capacity for D&I research within CTSAs through community engagement [47]. For example, community engagement and practice-based research networks (PBRNs) [48] are central to D&I, and many CTSAs already have expertise in community engagement, PBRNs, and existing Community Advisory Boards, which D&I researchers could learn from as part of "best practices" in engaging with and learning from existing networks of patients, clinicians, or other community partners.…”
Section: Ctsa Site Characteristicsmentioning
confidence: 99%
“…Originally conceived as a method to enhance the adoption and integration of medical innovations into everyday clinical practice [18,19], several CTSA hubs have recognized that similar processes can enhance the translational research process. Instructive examples [20,21] and a theoretical model for integrating D&I into a translational research framework have been published [20]. Since these studies have demonstrated that D&I efforts can enhance the impact of a wide range of CTSA activities, the techniques we describe can help CTSA leaders prioritize areas where D&I resources, which are often in short supply, are best allocated.…”
Section: Discussionmentioning
confidence: 99%
“…Until vaccines are more broadly implemented for infants and young children, a nimble response to COVID-19 is required. CTSA-funded community-based partnerships are very well-described [27,28], including community engagement programmatic responses with metrics generated by the COVID-19 pandemic [29,30], but this report highlights one of the few community engagement responses to the pandemic that is uniquely child health oriented. An increased focus on the importance of community-based partnerships that are uniquely concerned with child health issues is an important goal for future collaborations and will help address the underrepresentation of children in clinical research as we continue to confront these challenges in the post-pandemic world [31].…”
Section: Limitationsmentioning
confidence: 96%